2013
DOI: 10.1038/ncomms2869
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-induced encapsulation of liquids by destabilization of granular rafts

Abstract: Droplets and bubbles coated by a protective armour of particles find numerous applications in encapsulation, stabilization of emulsions and foams, and flotation techniques. Here we study the role of a body force, such as in flotation, as a means of continuous encapsulation by particles. We use dense particles, which self-assemble into rafts, at oil-water interfaces. We show that these rafts can be spontaneously or controllably destabilized into armoured oil-inwater droplets, which highlights a possible role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 31 publications
4
80
0
Order By: Relevance
“…The qualitative change to the flotation of particles caused by other nearby objects is now well documented [22][23][24] . At macroscopic scales, rafts of dense objects float significantly deeper in the liquid than they do in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative change to the flotation of particles caused by other nearby objects is now well documented [22][23][24] . At macroscopic scales, rafts of dense objects float significantly deeper in the liquid than they do in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the proximity of other particles in the raft constrains the menisci to be more horizontal than they would be for an isolated particle: the particles thus sink deeper into the liquid so that hydrostatic pressure can make up for the loss of supporting force from surface tension. Indeed, this effect can be so dramatic that dense particles that are able to float in isolation may actually sink in the proximity of enough other floating particles 22,23 . While the dramatic loss of floating stability is unlikely to be relevant at the very small scales of colloidal particles, the observation that their vertical force balance may be affected by the presence of other particles is likely to be robust.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we study the self-encapsulation of a granular system consisting of hydrophobic sand [17][18][19][20] under water. This system self-generates a skin which encapsulates dry hydrophobic sand-grains and stabilizes the trapped air (bubble) against the force of buoyancy.…”
Section: Introductionmentioning
confidence: 99%
“…The paper also explores the mechanical properties of this system at multiple scales: from the pinning of the three phase contact line at the roughness scale of the particle, plastic flow at the grain-scale, to sample-spanning mechanical responses. It may be noted here that while hydrophilic granular systems -both dry and wet -are widely studied [5,21], hydrophobic sand grains submerged in a non-wetting liquid like water remain largely unexplored [17][18][19][20] even though such systems are of practical importance, especially in pharmaceutical, food and petroleum industries where newer encapsulation strategies are in great demand [22].…”
Section: Introductionmentioning
confidence: 99%
“…Soft matter systems may also exhibit intriguing behaviors ruled by interfacial stresses, as opposed to the bulk stresses discussed above. For example, recent work has shown that the addition of colloidal particles at the interface between two (immiscible) fluids may modify profoundly the mechanical properties of the interface, by imparting it mechanical rigidity as in "bijels" [20,21] or in non-spherical "armoured" bubbles [22,23], or by protecting bubbles and drops from coalescence [24]. Recently, we have explored the role of interfacial stresses in colloidal systems in what is arguably the most minimalist experimental configuration: the sharp interface between a colloidal suspension and its own solvent [25].…”
Section: Introductionmentioning
confidence: 99%